2011
DOI: 10.1128/jvi.02093-10
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 16 (HPV-16) Genomes Integrated in Head and Neck Cancers and in HPV-16-Immortalized Human Keratinocyte Clones Express Chimeric Virus-Cell mRNAs Similar to Those Found in Cervical Cancers

Abstract: Many human papillomavirus (HPV)-positive high-grade lesions and cancers of the uterine cervix harbor integrated HPV genomes expressing the E6 and E7 oncogenes from chimeric virus-cell mRNAs, but less is known about HPV integration in head and neck cancer (HNC).Mucosal high-risk (HR) human papillomavirus (HPV) types are found in nearly 100% of carcinomas of the uterine cervix, many anogenital cancers, and ϳ25% of head and neck cancers (HNC) (9, 13, 42). The most common HR HPV is type 16, found in over 50% of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 54 publications
3
61
0
3
Order By: Relevance
“…In an in-vitro study of HPV-transfected keratinocytes, integration sites were detected in various chromosomal locations but also in or near genes encoding growth control proteins [32]. This supports the idea of clonal selection by HPV integration towards more aggressive tumors.…”
Section: Hpv Dna Integrationsupporting
confidence: 63%
“…In an in-vitro study of HPV-transfected keratinocytes, integration sites were detected in various chromosomal locations but also in or near genes encoding growth control proteins [32]. This supports the idea of clonal selection by HPV integration towards more aggressive tumors.…”
Section: Hpv Dna Integrationsupporting
confidence: 63%
“…More than 200 different human papillomavirus (HPVs) types have been characterized (Psyrri et al, 2008), and at least 40 types can infect human genital tract (Munoz et al, 2003), of which HPV16 and HPV18 as main high-risk types are more closely linked with malignant tumors. Recent study has shown that HPV genomes integrated in head and neck cancer express chimeric virus-cell mRNAs, which is similar to those found in cervical cancers (Lace et al, 2011). HPVassociated OSCCs tend to be poorly differentiated with basaloid features in histology, frequently presenting at an advanced stage.…”
Section: Introductionmentioning
confidence: 55%
“…In OPSCC, data concerning the frequency of HPV integration are limited [15][16][17]. We previously reported that we could detect no evidence of HPV integration from 40 HPV 16 positive OPSCC by using restriction site oligonucleotide PCR (RSO-PCR) [18], while the same method was able to identify HPV cellular junctions in many cervical cancers [5,11,19,20].…”
Section: Introductionmentioning
confidence: 98%